Recherche littéraire / Literary Research Automne / Fall 2020 - Maufort, Marc (Recherche littéraire / Literary Research, 2020)
Julie K. Allen, Eugene L. Arva, Jean Bessière, Helena Carválho Buescu, Vanessa Byrnes, Chloé Chaudet, Yves Clavaron, Christophe Den Tandt, Catherine Depretto., Theo D'haen, Caius Dobrescu, Dong Yang, Brahim El Guabli, Nikki Fogle, Gerald Gillespie, Kathleen Gyssels, Oliver Harris, Sándor Hites, Michelle Keown, S Satish Kumar, Jacques Marx, Jessica Maufort, Marc Maufort, Jopi Nyman, David O'Donnell, Liedeke Plate, Judith Rauscher, Haun Saussy, Karen-Margrethe Simonsen, Chris Thurman, Anne Williams, Janet M. Wilson, Chantal Zabus, Gang Zhou